2014
DOI: 10.1007/8904_2014_305
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation and Dantrolene for Secondary Dystonia in X-Linked Adrenoleukodystrophy

Abstract: Deep brain stimulation (DBS) has been used to treat secondary dystonias caused by inborn errors of metabolism with varying degrees of effectiveness. Here we report for the first time the application of DBS as treatment for secondary dystonia in a 22-year-old male with X-linked adrenoleukodystrophy (X-ALD). The disease manifested at age 6 with ADHD, tics, and dystonic gait, and deteriorated to loss of ambulation by age 11, and speech difficulties, seizures, and characteristic adrenal insufficiency by age 16. DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…94-99 The most common side effects of dantrolene are dizziness, drowsiness, light headedness, headaches, anorexia, diarrhea, nausea, and vomiting. Chronic oral use can be associated with liver dysfunction.…”
mentioning
confidence: 99%
“…94-99 The most common side effects of dantrolene are dizziness, drowsiness, light headedness, headaches, anorexia, diarrhea, nausea, and vomiting. Chronic oral use can be associated with liver dysfunction.…”
mentioning
confidence: 99%
“…Less is known about the impact of DBS on rarer inherited causes of dystonia, in particular heredodegenerative diseases with a phenotype characterized by a progressive generalized dystonia, parkinsonism and other neurological signs (Table 3) [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78].…”
Section: Globus Pallidus Pars Interna Deep Brain Stimulationmentioning
confidence: 99%
“…Very recently, a doubleblind, randomized crossover trial on GPi DBS has reported a significant improvement in tic severity, with an overall acceptable safety profile [99 && ]. Wilson's disease [62] Neuro-acantocytosis [63] Senataxin mutation-related dystonia [64] Paroxysmal nonkinesigenic dyskinesia [65] Stereotypies in autism spectrum disorders à [66] Variable/negative results DRD (tyrosine hydroxylase with status dystonicus) [67] Lesch-Nyhan [68] Cockayne syndrome [69] Dystonia-deafness [70] Rapid-onset dystonia-parkinsonism [71] GM1 gangliosidosis [72] X-linked adrenoleukodystrophy [73] Homocystinuria [74] SCA 1 [75] SCA 17 [64] Ataxia-telangiectasia Ãà Klinefelter syndrome [76] Tremor associated with demyelinating neuropathy ÃÃà [77] Orthostatic tremor [78] Methylmalonic …”
Section: Unilateral or Bilateral?mentioning
confidence: 99%